2004
DOI: 10.1124/dmd.32.8.779
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine Up-Regulates P-Glycoprotein Independent of the Pregnane X Receptor

Abstract: ABSTRACT:P-Glycoprotein (P-gp) and cytochrome P450 3A4 (CYP3A4) constitute a physiologic barrier in the intestine for many of the same substrates. Their expression can be influenced by nuclear receptor NR1I2 (pregnane X receptor; PXR), which acts as a receptor for various endobiotics and xenobiotics. However, P-gp and CYP3A4 are not identical in anatomic localization, suggesting unique as well as shared regulatory mechanisms of gene expression. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 28 publications
3
28
0
1
Order By: Relevance
“…To address this possibility, first we have studied the effect of tetrac on expression of Pglycoprotein, SOD, and GST-p and found that expression of none of these genes was significantly altered (Fig 3). Others have shown that agonist thyroid hormone can increase expression of P-gp [26,27]. Tetrac, at the concentrations used, exerts its thyroid hormone antagonist activity primarily at the integrin receptor.…”
Section: Discussionmentioning
confidence: 97%
“…To address this possibility, first we have studied the effect of tetrac on expression of Pglycoprotein, SOD, and GST-p and found that expression of none of these genes was significantly altered (Fig 3). Others have shown that agonist thyroid hormone can increase expression of P-gp [26,27]. Tetrac, at the concentrations used, exerts its thyroid hormone antagonist activity primarily at the integrin receptor.…”
Section: Discussionmentioning
confidence: 97%
“…5). Mitin et al 19) reported that P-gp, but not CYP3A2, is induced by LTX (100 mM) in human colon carcinoma cells (LS180 and Caco-2) in vitro, and the induction is mediated by thyroid hormone receptor (TR) rather than PXR. Our results are consistent with this.…”
Section: Discussionmentioning
confidence: 99%
“…In various cells, this antibiotic induces P-glycoprotein, thus notably altering the physiology of these cells (Greiner et al 1999;Asghar et al 2002;Collett et al 2004;Granzotto et al 2004;Mitin et al 2004).…”
Section: Resultsmentioning
confidence: 98%